Efektivitas Pembelajaran Ilmu Tajwid terhadap Kemampuan Membaca Al-Qur’an Siswa Kelas XII RPL 2 SMKN 1 Wonosobo - Marfuah Marfuah; Dena Nafikhatul Aulia; Ina Niatul Maidah; Ati’il Khusna; Mailatussakinah Mailatussakinah; Mufida Salsabila; Eka Faena Guslaila; Ahmad Khoiri (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
This study aims to describe the effectiveness of tajwid learning and its influence on the Qur’an reading ability of grade XII RPL 2 students at SMKN 1 Wonosobo. The research employs a qualitative method with a descriptive-analytical approach. Data were collected through classroom observation and interviews with both the teacher and selected students. The findings indicate that the tajwid learning process in grade XII RPL 2 has been quite effective, as it is conducted in accordance with the established rules of tajwid. The use of varied teaching methods, particularly those emphasizing reading practice, has positively influenced students’ ability to recite the Qur’an correctly. Most students are able to read fluently, observe the proper length of vowels, and articulate the letters according to their correct makhraj. Nevertheless, a small number of students have not yet fully mastered the application of makharijul letters consistently, thus requiring further guidance and practice. Overall, tajwid learning in this class contributes significantly to the improvement of Qur’an reading skills, both in terms of fluency and accuracy. Furthermore, this study highlights that mastery of tajwid is crucial for preserving the authenticity of Qur’anic recitation as well as enhancing students’ understanding and appreciation of the Qur’an. Therefore, tajwid instruction not only develops technical reading skills but also plays an important role in fostering religious and spiritual values among learners.